Prototype of Dual DDS FMCW Transmitter for L-Band Synthetic Aperture Radar - Edwar, E.; Munir, Achmad (JMECS (Journal of Measurements, Electronics, Communications, and Systems); Vol 4 No 1 (2018): JMECSDO - 10.25124/jmecs.v4i1.1694, 2018)
One of the popular remote sensing technique is remote sensing using radar technology such as Synthetic Aperture Radar (SAR). In this paper, a compact SAR prototype transmitter was designed so it could be installed in small platform. This SAR transmitter was designed to generate a frequency modulated continuous wave (FMCW) using direct digital synthesizer (DDS) integrated with RF front end modules such as analog filter and power amplifier. The bandwidth of the radar spectrum is 10 MHz, and the carrier frequency used is 1.27 GHz. The L-Band has been chosen as the carrier signal in order to detect the target (trees). The payload was designed for aerial vehicle, hence the choice of components should be as small as possible. The FMCW-SAR transmitter was implemented by using DDS module AD9850 and integrated with another RF component. The FMCW-SAR transmitter produces the transmit power about -17.67 dBm.